Labor economics - Borjas, George J. (McGraw Hill Education, 2016)
Labor Economics, seventh edition by George J. Borjas provides a modern introduction to labor economics, emphasizing both theory and empirical evidence. The book uses many examples drawn from state-of-the-art studies in labor economics literature. The author introduces, through examples, methodological techniques that are commonly used in labor economics to empirically test various aspects of the theory. Labor Economics is thoroughly integrated with the adaptive digital tools available in McGraw-Hill's LearnSmart Advantage Suite, proven to increase student engagement and success in the course